Snail Track Lesion with Flat Keratometry in Anterior Segment Dysgenesis Caused by a Novel FOXC1 Variant - Skalicka, Pavlina; Jedlickova, Jana; Horinek, Ales; Trkova, Marie; Davidson, Alice E; Tuft, Stephen J; Dudakova, Lubica; Liskova, Petra (Journal of clinical medicine, 2022)
We report the phenotype of a 15-year-old female patient with anterior segment dysgenesis (ASD) caused by a novel heterozygous loss-of-function FOXC1 variant. The proband underwent an ophthalmic examination as well as a molecular genetic investigation comprising exome sequencing, a single nucleotide polymorphism array to access copy number and Sanger sequencing to exclude non-coding causal variants. There was bilateral mild iris hypoplasia with pupil deformation and iridocorneal adhesions. In addition to these features of ASD, the corneas were flat, with mean keratometry readings of 38.8 diopters in the right eye and 39.5 diopters in the left eye. There was a snail track lesion of the left cornea at the level of the Descemet membrane. The central corneal endothelial cell density was reduced bilaterally at 1964 and 1373 cells/mm2 in the right and left eyes, respectively. Molecular genetic analysis revealed that the proband was a carrier of a novel heterozygous frameshifting variant in FOXC1, c.605del p.(Pro202Argfs*113). Neither parent had this change, suggesting a de novo origin which was supported by paternity testing. We found no possibly pathogenic variants in the other genes associated with posterior corneal dystrophies or ASD. Further studies are warranted to verify whether there is a true association between snail track lesions, corneal flattening, and pathogenic variants in FOXC1.